2021
DOI: 10.21037/atm-20-7355
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of exosomes in vascular calcification

Abstract: Vascular calcification (VC) is the abnormal deposition of calcium, phosphorus, and other minerals in the vessel wall and can be commonly observed in diabetes, chronic kidney disease, and chronic inflammatory disease. It is closely associated with mortality from cardiovascular events. Traditionally, calcification is considered as a degenerative disease associated with the aging process, while increasing evidence has shown that the occurrence and development of calcification is an active biological process, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…Furthermore, an increase in reactive oxygen species (ROS) production is involved in VSMC osteochondrogenic trans-differentiation during the VC process ( Tóth et al, 2020 ; Hu et al, 2021 ). Recent studies have highlighted the role of extracellular vesicles (EVs) in VC ( Hodroge et al, 2017 ; Mansour et al, 2020 ; Yaker et al, 2020 ; Qin et al, 2021 ). These membrane-bound vesicles, secreted by prokaryotic and eukaryotic cells ( Woith et al, 2019 ), can be of various origins, depending on their mode of biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an increase in reactive oxygen species (ROS) production is involved in VSMC osteochondrogenic trans-differentiation during the VC process ( Tóth et al, 2020 ; Hu et al, 2021 ). Recent studies have highlighted the role of extracellular vesicles (EVs) in VC ( Hodroge et al, 2017 ; Mansour et al, 2020 ; Yaker et al, 2020 ; Qin et al, 2021 ). These membrane-bound vesicles, secreted by prokaryotic and eukaryotic cells ( Woith et al, 2019 ), can be of various origins, depending on their mode of biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that exosomes share many characteristics of matrix vesicles (MVs), which are unique extracellular membrane-bound microparticles that serve as initial sites for mineral formation ( Qin et al, 2021 ). Exosomes are important transporters of molecules that drive vascular calcification (VC).…”
Section: Endothelial Exosomesmentioning
confidence: 99%
“…In recent years, exosomes haves gained increasing attention in the cardiovascular field, largely owing to their ability to transmit biological information between adjacent and distant cells ( 14 ). Previous reviews mostly focused on the underlying mechanisms of exosomes in cardiovascular diseases ( 15 , 16 ), yet ignore the cellular crosstalk among different vessel layers. Recent studies have found that endothelial cells, VSMCs, fibroblast, macrophages, and even circulation blood cells around vascular wall environments respond actively to stimulus and participate in vascular calcification via transdifferentiating, cytokine secretion, extracellular vesicle synthesis, angiogenesis regulation, and hemodynamics.…”
Section: An Introduction To Exosomesmentioning
confidence: 99%